Sistem Pengambil Keputusan untuk Menentukan Kelayakan Penerima Kredit Mobil di PT. Adira Finance Cabang Kota Pasuruan - Prakasa Putra Irawan; M Misdram; Ratih Fitri Aini (JOINTECS (Journal of Information Technology and Computer Science), 2017)
PT. Adira Finance branch at Pasuruan city is one of enterprise that budged in funding sector and vehicle insurance. Advisability policy give credit a car for customer still use conventional method and need a lot of time to give advisability policy give credit to customer. The purpose of this study is to built a software as device to help make decision for the leader in giving credit to customer and to make easier the customer in delivery information about submission their credit. The methodology of this research is field research , interview and library research. Determination of the feasibility of using five credit recipient C. Decision Support System credit aplication can make easier in take a decision to determine advisability a customer in accept credit. It can take in hand a process for renewal customer data, the data of car, and the reporting process so. It have documentation about a good software.